Association of the metabolic syndrome with mortality and major adverse cardiac events: A large chronic kidney disease cohort - Pammer, Lorenz M.; Lamina, Claudia; Schultheiss, Ulla T.; Kotsis, Fruzsina; Kollerits, Barbara; Stockmann, Helena; Lipovsek, Jan; Meiselbach, Heike; Busch, Martin; Kronenberg, Florian; Eckardt, Kai-Uwe (Journal of Internal Medicine, 2021)
Background Metabolic syndrome with its key components insulin resistance, central obesity, dyslipidaemia, and hypertension is associated with a high risk for cardiovascular events and all-cause mortality in the general population. However, evidence that these findings apply to patients with chronic kidney disease (CKD) with moderately reduced estimated glomerular filtration rate and/or albuminuria is limited. Objectives We aimed to investigate the association between metabolic syndrome and its components with all-cause mortality and cardiovascular outcomes in CKD patients. Methods Prospective observation of a cohort of 5110 CKD patients from the German Chronic Kidney Disease study with 3284 (64.3%) of them having a metabolic syndrome at baseline. Results During the follow-up of 6.5 years, 605 patients died and 650 patients experienced major cardiovascular events. After extended data adjustment, patients with a metabolic syndrome had a higher risk for all-cause mortality (hazard ratio [HR] = 1.26, 95% confidence interval [CI]: 1.04-1.54) and cardiovascular events (HR = 1.48, 95% CI: 1.22-1.79). The risk increased steadily with a growing number of metabolic syndrome components (increased waist circumference, glucose, triglycerides, hypertension and decreased HDL cholesterol): HR per component = 1.09 (95% CI: 1.02-1.17) for all-cause mortality, and 1.23 (95% CI: 1.15-1.32) for cardiovascular events. This resulted in hazard ratios between 1.50 and 2.50 in the case of four or five components present. Analysis of individual components of metabolic syndrome showed that the glucose component led to the highest increase in risk for all-cause mortality (HR = 1.68, 95% CI: 1.38-2.03) and cardiovascular events (HR = 1.81, 95% CI: 1.51-2.18), followed by the HDL cholesterol and triglyceride components. Conclusions We observed a high prevalence of metabolic syndrome among patients with moderate CKD. Metabolic syndrome increases the risk for all-cause mortality and cardiovascular events. The glucose and lipid components seem to be the main drivers for the association with outcomes.
CRIS-Team WoS Importer:2021-08-13